Distribution of Early, Middle, and Late Noachian cratered surfaces in the Martian highlands: Implications for resurfacing events and processes. Issue 2 (25th February 2013) - Irwin, Rossman P.; Tanaka, Kenneth L.; Robbins, Stuart J.
Abstract: [1] Most of the geomorphic changes on Mars occurred during the Noachian Period, when the rates of impact crater degradation and valley network incision were highest. Fluvial erosion around the Noachian/Hesperian transition is better constrained than the longer‐term landscape evolution throughout the Noachian Period, when the highland intercrater geomorphic surfaces developed. We interpret highland resurfacing events and processes using a new global geologic map of Mars (at 1:20, 000, 000 scale), a crater data set that is complete down to 1 km in diameter, and Mars Orbiter Laser Altimeter topography. The Early Noachian highland (eNh) unit is nearly saturated with craters of 32–128 km diameter, the Middle Noachian highland (mNh) unit has a resurfacing age of ~4 Ga, and the Late Noachian highland unit (lNh) includes younger composite surfaces of basin fill and partially buried cratered terrain. These units have statistically distinct ages, and their distribution varies with elevation. The eNh unit is concentrated in the high‐standing Hellas basin annulus and in highland terrain that was thinly mantled by basin ejecta near 180° longitude. The mNh unit includes most of Arabia Terra, the Argyre vicinity, highland plateau areas between eNh outcrops, and the Thaumasia range. The lNh unit mostly occurs within highland basins. Crater depth/diameter ratios do not vary strongly between the eNh and mNh units, although crater losses to Noachian resurfacing appear greater in lower lying areas. Noachian resurfacing was spatially non‐uniform, long‐lived, and gravity‐driven, more consistent with arid‐zone fluvial and aeolian erosion and volcanism than with air fall mantling or mass wasting. Key Points: The Early Noachian highland unit is nearly saturated with 32‐128 km craters. Noachian resurfacing depended on regional and topographic location. Resurfacing likely included fluvial, aeolian, and volcanic processes.